2018
DOI: 10.11124/jbisrir-2017-003433
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Madura foot: a systematic review

Abstract: Therapy for Madura foot is informed by case series and case reports which provide low level evidence for practice. Antimicrobials in conjunction with surgery lead to resolution of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
0
6
0
2
Order By: Relevance
“…Mycetoma, a chronic [ 1 ] infection of the skin and underlying structures [ 2 ], leads to significant disability [ 3 ] and mortality [ 4 ]. It can be caused by any one of several fungi (eumycetoma) [ 5 ] or bacteria (actinomycetoma) [ 6 ], some more common than others ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mycetoma, a chronic [ 1 ] infection of the skin and underlying structures [ 2 ], leads to significant disability [ 3 ] and mortality [ 4 ]. It can be caused by any one of several fungi (eumycetoma) [ 5 ] or bacteria (actinomycetoma) [ 6 ], some more common than others ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…4,12,13,16,17 Mycetoma is caused by ubiquitous fungi (eumycetoma) or filamentous bacteria (actinomycetoma), found in soil and plants of endemic countries, with more than 50 species identified. 2,3,12,14,15 It is most frequently caused by Nocardia, Streptomyces, and Actinomadura. 2,4,11,17 The disease evolves within weeks to years after skin trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Highlighting the need for more actinomycetoma treatment and prognosis information, a systematic review of reports of mycetoma treatment between 1950 and 2016 revealed only 21 actinomycetoma cases with assessable outcomes (cure, recurrence, or mortality) [17]. Nevertheless, the systematic review did not include important Sudanese, Indian, Senegalese, and Mexican case series previously published and synthesized by Zijilstra et al in 2016 [5].…”
Section: Discussionmentioning
confidence: 99%